2018
DOI: 10.1111/lsi.12265
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Hysteria: Legal Signals as Producers of Siting Conflicts Over Sexually Violent Predator Placements

Abstract: Sexually violent predator (SVP) statutes define some sex offenders as dangerous enough to be segregated from society, but then require their release into local communities. This article examines how decision makers and community members interpret and respond to this inherent contradiction during disputes over SVP placements. The article departs from traditional moral panic explanations of reactions to sex offenders by linking literature on local siting conflicts to insights from legal mobilization studies in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 45 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…The first project focused on differential community attitudes and responses to living in highcrime communities (Leverentz, 2011(Leverentz, , 2012. The second project focused on community responses to SVP placements in two communities (Williams, 2013(Williams, , 2016. Across the two datasets, we captured urban and rural, predominantly Black and predominantly White, high-and low-crime communities (see table 1 for a summary of the four sites).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first project focused on differential community attitudes and responses to living in highcrime communities (Leverentz, 2011(Leverentz, , 2012. The second project focused on community responses to SVP placements in two communities (Williams, 2013(Williams, , 2016. Across the two datasets, we captured urban and rural, predominantly Black and predominantly White, high-and low-crime communities (see table 1 for a summary of the four sites).…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis is based on data collected for two studies on social control and community responses to crime. The first study focused on how urban communities defined crime and criminals, broadly speaking, and how this was shaped by community context (Leverentz, 2011(Leverentz, , 2012; the second examined how and why urban and rural communities responded to sexually violent predator (SVP) placements in their towns (Williams, 2013(Williams, , 2016. Together, these data allow us to expand existing theories about the processes through which communities and political and legal institutions shape crime-control efforts across demographically and geopolitically different communities.…”
mentioning
confidence: 99%
“…Examining one state in particular, Goodman, Page, and Phelps (2017) found that struggles between activists, bureaucrats, and other low-level actors contributed to changes in criminal justice policies. Their findings reflect increasing calls for scholars to examine the local contexts of policymaking in order to understand how and why policies vary across places (Williams 2018b). Despite this new trend in analyzing policymaking at the state level, few studies have directly examined the policy processes that contribute to the proliferation of residence restriction laws across states.…”
Section: Sex Offender Residence Restrictionsmentioning
confidence: 98%
“…Other scholars have found that the instrumental effects of symbolic laws may vary across contexts. One example includes sexually violent predator statutes, which, according to Williams (2018b), affect communities differently based on communities' relationships with political and legal authorities. Similarly, mandatory sentencing laws, while having little impact on punishment practices broadly, have affected some sentences in particular areas for particular cases (Sutton 2013).…”
Section: Sex Offender Residence Restrictions As Symbolic Lawmentioning
confidence: 99%
See 1 more Smart Citation